Serotonin receptor modulators in the treatment of irritable bowel syndrome - Lackner, Jeffrey (Therapeutics and clinical risk management, 2008)
The aim of this article is to review the pathophysiology and clinical role of serotonin receptor modulators used in the treatment of irritable bowel syndrome. Serotonin is an important monoamine neurotransmitter that plays a key role in the initiation of peristaltic and secretory refl exes, and in modulation of visceral sensations. Several serotonin receptor subtypes have been characterized, of which 5HT3, 5HT4, and 5HT1b are the most important for GI function. 5HT4 agonists (eg, tegaserod) potentiate peristalsis initiated by 5HT1 receptor stimulation. 5HT4 agonists are therefore useful in constipation predominant form of IBS and in chronic constipation. 5HT3 antagonists (Alosetron and Cilansetron) prevent the activation of 5HT3 receptors on extrinsic afferent neurons and can decrease the visceral pain associated with IBS. These agents also retard small intestinal and colonic transit, and are therefore useful in diarrhea-predominant IBS. Tegaserod has been demonstrated in several randomized, placebo controlled trials to relieve global IBS symptoms as well as individual symptoms of abdominal discomfort, number of bowel movements and stool consistency. Several randomized, controlled trials have shown that alosetron relieves pain, improves bowel function, and provides global symptom improvement in women with diarrhea-predominant irritable bowel syndrome. However, ischemic colitis and severe complications of constipation have been major concerns leading to voluntary withdrawal of Alosetron from the market followed by remarketing with a comprehensive risk management program.